Organoids and Microphysiological Systems: New Tools for Ophthalmic Drug Discovery - Bai, Jing; Wang, Chunming (Frontiers in Pharmacology, 2020)
Organoids preserve the inherent complexity of the cellular system. Engineered microphysiological systems (MPS) integrated with organoids have advantages in mimicking a precisely controlled geometrical, physical and biochemical microenvironment, which allows for real-time monitoring of cell-cell interactions. Recently, these two technologies hold significant promise to study ocular physiology and diseases by recapitulating specific eye tissue microstructures in vitro. This mini-review starts with defining organoid/MPS will be defined and briefly introducing the methods for generating organoids and engineering MPS. Then, it discusses the current status of organoids and MPS models in retina, cornea surrogates, and other ocular tissue physiological/disease models. Finally, future perspectives on organoid/MPS are discussed. Organoids and MPS closely recapitulate the in vivo microenvironment and provide new understandings on organ functions and novel approaches in drug development.